Employee assessment of their technological redundancy. (3rd July 2017) - Brougham, David; Haar, Jarrod
ABSTRACT: Many futurists and business people suggest that we are in the midst of the fourth industrial revolution because of rapid advancements in smart technology, artificial intelligence, automation, robotics, and algorithms (STAARA). However, very little research has been conducted on how employees view their jobs and careers in the age of these potential changes. Structural equation modelling was used on a sample of 196 employees to test a number of job-related predictors regarding employees' perceptions of their job insecurity from STAARA: job control, job complexity, job repetition, and STAARA awareness. These employee-rated predictors were then used to predict STAARA redundancy. Overall, all constructs played important roles in understanding the prediction of STAARA redundancy. Unusually, STAARA awareness was found to be negatively related to STAARA redundancy, indicating that employees may not be the best judge of technology's potential to replace their jobs. The implications are important when we consider how employees assess their jobs and long-term career prospects in relation to STAARA.